XGLM-564M Performance Degradation on Imbalanced Educational Dialogue Datasets Across Languages and Difficulty Levels - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 9 peer-reviewed papers addressing the following research question: How does the performance degradation of XGLM-564M on imbalanced educational dialogue datasets vary between Indonesian and English across different difficulty levels. 13 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.6/10. This report is a machine-generated literature
Machine-generated literature synthesis.